2021
DOI: 10.1186/s12879-021-06820-2
|View full text |Cite
|
Sign up to set email alerts
|

The serotype distribution of Streptococcus agalactiae (GBS) carriage isolates among pregnant women having risk factors for early-onset GBS disease: a comparative study with GBS causing invasive infections during the same period in Denmark

Abstract: Background We describe the serotype distribution of Streptococcus agalactiae (GBS) carriage isolates from women in labor and among GBS isolates causing invasive infections during the same period to see if the distribution of carriage serotypes reflects the GBS serotypes causing invasive diseases including early-onset disease (EOGBS). Methods Data on invasive isolates from 2019 including serotype, erythromycin and clindamycin susceptibility was retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Maternal GBS colonization is a major determinant of EOGBS infections in neonates. European studies have shown similarity in serotype distribution between maternal colonized GBS and iGBS, and this nding indicates that EOGBS infection is caused by GBS transmission from mother to newborn [13,14].…”
Section: Discussionmentioning
confidence: 68%
“…Maternal GBS colonization is a major determinant of EOGBS infections in neonates. European studies have shown similarity in serotype distribution between maternal colonized GBS and iGBS, and this nding indicates that EOGBS infection is caused by GBS transmission from mother to newborn [13,14].…”
Section: Discussionmentioning
confidence: 68%
“…They usually involve real-time PCR, either "in house" assays, dedicated to a number of PCR devices or molecular platforms. All of them differ in sensitivity and specificity of the results [1,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria were grown in Tryptone Soya Broth medium (TSB) (Oxoid CM0129) or on TSB agar plates (TSA) (Oxoid CM0131) at 37 °C with shaking (180 RPM). Identification and serotyping of the GBS isolates was performed as previously described [ 27 ]. The genomic sequence data for the 22 clinical isolates have been deposited at the European Nucleotide Archive (ENA) under Bioproject no.…”
Section: Methodsmentioning
confidence: 99%